Comparative Study of Otolith Growth Circle Patterns on the Psammoperca waigiensisin the Waters of Teluk BakauBintan Regency and Dompak Lama Tanjungpinang City Riau Islands Province - Achmad Sovy Yusaputra; Eddiwan Eddiwan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Psammoperca waigiensisis found in the waters of Teluk Bakau and Dompak Lama. Both of these waters have different water characteristics and conditions. This study aims to determine the pattern of growth circles on theP.waigiensis otoliths from the two waters. This research was conducted in March-April 2019. Sampling was carried out once a week in 1 month. Otoliths were sharpened using Windarti's (2017) otolith sharpening method, and the growth circle pattern on otoliths was observed under a binocular microscope. The results of the study found that fish originating from the waters of Teluk Bakauhave an otolith length range of 8-11 mm with an otolith weight of 0.0424-1227 gr, while otolith fish from Dompak Lama have a length of 8.2-10.7 mm with an otolith weight of 0.0447 -0,1096 gr. The circle of dark growth in fish from the waters of the Teluk Bakau is a maximum 3, while fish from the Dompak Lama a maximum 4. The distance of the fish otolith core in the two waters varies and does not have a special pattern. Keywords: Growth Circle, Dark Circle, Otolith, Sagita, Pssamoperca waigiensis